ANALISIS PERBANDINGAN ABNORMAL RETURN SAHAM SEBELUM DAN SESUDAH PENGUMUMAN RIGHT ISSUE - PRATAMA, I GEDE SURYA (E-Jurnal Manajemen, 2014)
Rights issue is one of corporate actions such as the issuance of new shares that are sold to existing shareholders through a rights issue in order to increase the capital of the company. Abnormal returns obtained from the difference between the actual return with the expected return. The method for calculating the expected return is the market model. This study uses event study to test the information content of the rights issue in the event window 11 days, 5 days before the announcement, 1 day and 5 days after the announcement of the announcement. The data used in this study to examine the results of the hypothesis using data from the Indonesian Capital Market Directory, a company that does the right issue around the period 2009-2012 with a sample size of 60 events right issue. The test results showed that there was no significant abnormal returns before and after the announcement of the rights issue. During the period estimates are the average abnormal return is less consistent.
Keywords: right issue; abnormal return; signaling theory; event study